Enhancing Beginning Reading and Writing Skills through Educational Multimedia Games and Direct Instruction - Tri Linda Darwati; Bachtiar S Bachri; Utari Dewi (Research Horizon, 2026)
Early reading and writing skills are fundamental competencies that support children’s subsequent academic achievement. However, conventional instructional approaches often fail to provide engaging learning experiences that effectively stimulate young learners’ literacy development. This study aimed to examine the effect of integrating educational multimedia games with the direct instruction learning model on the early reading and writing skills of first-grade students. A quantitative approach employing a quasi-experimental design with a non-equivalent control group was adopted. The participants consisted of first-grade students assigned to experimental and control groups. Data were collected through pre-tests, post-tests, classroom observations, and documentation, and analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, an independent samples t-test, and N-Gain analysis. The findings revealed that the experimental group achieved significantly higher post-test scores than the control group (84.30 vs. 69.80), with a statistically significant difference (p < 0.05). The experimental group also demonstrated a higher N-Gain score (0.61, moderate category) and greater classroom engagement. These findings indicate that integrating educational multimedia games with the direct instruction model effectively enhances early reading and writing skills by creating a more interactive, engaging, and meaningful learning environment for elementary school students.